2022
DOI: 10.3389/frai.2022.1011524
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of artificial intelligence among doctors and medical students in Syria: A cross-sectional online survey

Abstract: Artificial intelligence has been prevalent recently as its use in the medical field is noticed to be increased. However, middle east countries like Syria are deficient in multiple AI implementation methods in the field of medicine. So, holding these AI implementation methods in the medical field is necessary, which may be incredibly beneficial for making diagnosis more accessible and help in the treatment. This paper intends to determine AI's knowledge, attitude, and practice among doctors and medical students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 24 publications
5
22
2
Order By: Relevance
“…Currently, despite 84% of medical students lacking formal AI training, a higher proportion of them, relative to practicing physicians, see AI positively influencing their careers. 12 However, a 2022 study revealing limited understanding of AI among physicians and medical students 13 corresponds with our study's findings. Overall, these results underscore the importance of increased AI education in medicine, signaling its potential to boost acceptance and effective integration of AI in practice.…”
Section: Discussionsupporting
confidence: 89%
“…Currently, despite 84% of medical students lacking formal AI training, a higher proportion of them, relative to practicing physicians, see AI positively influencing their careers. 12 However, a 2022 study revealing limited understanding of AI among physicians and medical students 13 corresponds with our study's findings. Overall, these results underscore the importance of increased AI education in medicine, signaling its potential to boost acceptance and effective integration of AI in practice.…”
Section: Discussionsupporting
confidence: 89%
“…[13] This may be because Syria is now experiencing challenges with the internet and electricity as a result of a civil war that has lasted for more than 10 years. [14][15][16][17][18] Other studies reported greater proportions of internet addiction, such as Basem Salama et al research's in Al-Beheira Governorate, Egypt in 2020, which found that 47.5% of the subjects were afflicted by online addiction. [19] Mehdi Sayyah et al 2019.…”
Section: Discussionmentioning
confidence: 93%
“…[13] This may be because Syria is now experiencing challenges with the internet and electricity as a result of a civil war that has lasted for more than 10 years. [14–18] Other studies reported greater proportions of internet addiction, such as Basem Salama et al research’s in Al-Beheira Governorate, Egypt in 2020, which found that 47.5% of the subjects were afflicted by online addiction. [19] Mehdi Sayyah et al 2019.’s research on medical students in Iran found that (1.6% of them) used the internet normally, (47.4%) had a light internet addiction, (38.3% had a moderate addiction), and (12.9% had a severe degree of addiction).…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated with OpenEpi software (version 3.1), keeping the desired percentile at 50 and a confidence interval of 95%. The sample size for this study was calculated to be 323 (Swed et al, 2022). The framework of this study is presented in Figure 1.…”
Section: Methodsmentioning
confidence: 99%